Environmental stress and temporomandibular disorder (TMD) among members of a public university in Brazil - Ana Paula Sereni Manfredi; Paula Próspero Borelli Bortolleto; Ariovaldo Armando Silva; Izilda Esmênia Muglia Araújo; Sebastião Araújo; Laércio Luis Vendite (Brazilian Journal of Oral Sciences, 2015)
Temporomandibular disorder (TMD) is one of several somatic manifestations of stress. Several studies have shown that some patients with TMD suffer more anxiety than individuals without this condition. The aim of this study was to identify individuals with TMD and correlate with environmental stress among members of a public university. A proportional stratified probabilistic procedure was used to select 455 subject’s age 17-63 yrs consisted of students, staff and professors. The subjects were enlisted after lunch. TMD were diagnosed using a screening questionnaire based on the American Academy of Orofacial Pain (AAOP). Presence of TMD was defined based on pain in chewing or speaking, tired maxillae and pain in the head, neck and/or teeth. Environmental stress was diagnosed by using the Social Readjustment Rating Scale (SRRS).Gender distribution was similar among undergraduate and graduate students, but there were significant differences in the sex ratio of university staff (66.7% were females) and professors (81.8% were males). Prevalence of TMD influenced by stress among women was significantly greater than in men of the same age group (p=0.0001), and almost all individuals (90.9%) with TMD had a high level of stress (p=0.0082). These findings suggest that there is positive association between TMD and environmental stress.